2020
DOI: 10.1111/jocs.14431
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of treatments for uncomplicated type B intramural hematoma patients

Abstract: Objectives We aimed to investigate whether uncomplicated type B intramural hematoma (IMHB) patients with known evolution predictors could benefit from more aggressive therapy. Methods Retrospective analysis was performed in uncomplicated IMHB patients with evolution predictors between January 2001 and August 2018. Cox proportional hazard models were constructed to identify the specific factors associated with aorta‐related mortality. Results A total of 226 uncomplicated acute IMHB patients with evolution predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Of these, 17 studies were included in the present review, all observational and retrospective ( Figure 1 ). Two studies only reported on PAUs [ 11 , 14 ], two studies reported on PAUs and IMHs [ 5 , 10 ] and thirteen articles only concentrated on IMHs [ 12 , 13 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of these, 17 studies were included in the present review, all observational and retrospective ( Figure 1 ). Two studies only reported on PAUs [ 11 , 14 ], two studies reported on PAUs and IMHs [ 5 , 10 ] and thirteen articles only concentrated on IMHs [ 12 , 13 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…ARM timing was specified in five studies [ 10 , 18 , 19 , 21 , 24 ], and it occurred in the acute phase in 17/433 cases (3.9%). The number of patients undergoing intervention was reported in 12 studies [ 10 , 12 , 13 , 16 , 17 , 18 , 20 , 21 , 22 , 23 , 24 , 25 ], with a rate of 21% during follow-up (241/1147 cases) ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations